(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
A pin fins array as a heat sink along with a moist wood wool pad to serve as novel cooling system to cool PV panel has been used. The present cooling system was based on the evaporative cooling concept and extended area of heat transfer. The results gave enhancements in output power and panel’s efficiency about 32.7% and 31.5% respectively. This improvement in the module performance was attributed to the reduction in the operation temperature of the solar cell. The reduction in module temperature was about 26.05%.